2007
DOI: 10.1080/15248370701202471
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Proportional Reasoning: Effect of Continuous Versus Discrete Quantities

Abstract: This study examines the development of children's ability to reason about proportions that involve either discrete entities or continuous amounts. Six-, 8-and 10-year olds were presented with a proportional reasoning task in the context of a game involving probability. Although all age groups failed when proportions involved discrete quantities, even the youngest age group showed some success when proportions involved continuous quantities. These findings indicate that quantity type strongly affects children's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
166
6
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(193 citation statements)
references
References 31 publications
18
166
6
3
Order By: Relevance
“…Findings suggested that children as young as 8 years old were able to consider both components that constitute a proportion and integrate them in a normative proportional way 2 . These results stand in contrast to previous claims that proportional reasoning does not emerge before the age of 11 years (Moore et al, 1991;Noelting, 1980;Piaget & Inhelder, 1975) and confirm other findings that even younger children are able to reason about proportions (Acredolo et al, 1989;Boyer & Levine, 2012;Boyer et al, 2008;Jeong et al, 2007;Schlottmann, 2001;Singer-Freeman & Goswami, 2001;Sophian, 2000;Spinillo & Bryant, 1991, 1999. In line with previous paradigms showing earlier success in children's proportional reasoning, it is possible that the presentation of continuous proportional quantities and the nature of the response mode (spatial ratings that are more intuitively graspable) led to children's success on our proportional reasoning task.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Findings suggested that children as young as 8 years old were able to consider both components that constitute a proportion and integrate them in a normative proportional way 2 . These results stand in contrast to previous claims that proportional reasoning does not emerge before the age of 11 years (Moore et al, 1991;Noelting, 1980;Piaget & Inhelder, 1975) and confirm other findings that even younger children are able to reason about proportions (Acredolo et al, 1989;Boyer & Levine, 2012;Boyer et al, 2008;Jeong et al, 2007;Schlottmann, 2001;Singer-Freeman & Goswami, 2001;Sophian, 2000;Spinillo & Bryant, 1991, 1999. In line with previous paradigms showing earlier success in children's proportional reasoning, it is possible that the presentation of continuous proportional quantities and the nature of the response mode (spatial ratings that are more intuitively graspable) led to children's success on our proportional reasoning task.…”
Section: Discussioncontrasting
confidence: 57%
“…That is, children's formal fraction knowledge may have helped them to encode spatial proportions and to reproduce them on the rating scale. Even though this possibility cannot be eliminated by our correlational results, it seems unlikely in light of many studies (Acredolo et al, 1989;Boyer & Levine, 2012;Boyer et al, 2008;Jeong et al, 2007;Schlottmann, 2001;Singer-Freeman & Goswami, 2001;Sophian, 2000;Spinillo & Bryant, 1991, 1999 showing signs of proportional reasoning at an age when understanding of formal fractions is not present (Hecht & Vagi, 2010;Schneider & Siegler, 2010;Stafylidou & Vosniadou, 2004). Nonetheless, future studies using longitudinal designs or training components are needed to pin down the causal direction of the relation we have identified.…”
Section: The Relation Between Proportional Reasoning and Fraction Undmentioning
confidence: 79%
See 1 more Smart Citation
“…In fact, research over the past several decades shows that young children, and perhaps even infants, are sensitive to proportional relations (e.g., Denison & Xu, 2010;Jeong, Levine, & Huttenlocher, 2007;McCrink & Wynn, 2007;Sophian, 2000;Xu & Garcia, 2008). However, these studies also show that there are limits to children's early sense of proportion.…”
Section: Introductionmentioning
confidence: 94%
“…Children's apparent lack of competence could stem not from difficulties in reasoning about discrete quantities per se, but from the tendency to count when a task affords the opportunity (Jeong, Levine, & Huttenlocher, 2007;Boyer, Levine, & Huttenlocher, 2008). …”
Section: Multiplicative Transformationsmentioning
confidence: 99%